Improving Estrogenic Compound Screening Efficiency by Using Self-Modulating, Continuously Bioluminescent Human Cell Bioreporters Expressing a Synthetic Luciferase. (10th January 2019) - Xu, Tingting; Kirkpatrick, Andrew; Toperzer, Jody; Ripp, Steven; Close, Dan
Abstract: A synthetic bacterial luciferase-based autobioluminescent bioreporter, HEK293ERE/Gal4-Lux, was developed in a human embryonic kidney (HEK293) cell line for the surveillance of chemicals displaying endocrine disrupting activity. Unlike alternative luminescent reporters, this bioreporter generates bioluminescence autonomously without requiring an external light-activating chemical substrate or cellular destruction. The bioreporter's performance was validated against a library of 76 agonistic and antagonistic estrogenic endocrine disruptor chemicals and demonstrated reproducible half maximal effective concentration (EC50 ) values meeting the U.S. Environmental Protection Agency (EPA) guidelines for Tier 1 endocrine disrupting chemical screening assays. For model compounds, such as the estrogen receptor (ER) agonist 17β-estradiol, HEK293ERE/Gal4-Lux demonstrated an EC50 value (7.9 × 10 −12 M) comparable to that of the current EPA-approved HeLa-9903 firefly luciferase-based estrogen receptor transcription assay (4.6 × 10 −12 M). Screening against an expanded array of common ER agonists likewise produced similar relative effect potencies as compared with existing assays. The self-initiated autobioluminescent signal of the bioreporter permitted facile monitoring of the effects of endocrine disrupting chemicals, which decreased the cost and hands-on time required to perform these assays. These characteristics make the HEK293ERE/Gal4-Lux bioreporter potentially suitable as a high-throughput human cell-based assay for screening estrogenic activity.